HEALING AND THE ENVIRONMENT IN AMERICAN INDIAN BIOGRAPHIES - Shaheena Ayub Bhatti (European Scientific Journal, ESJ, 2014)
This paper explores a case study of traditional healing practices shown in the biographies of two medicine men – Rolling Thunder of the Cherokee-Shoshone tribe and Mad Bear Anderson of the Tuscarora tribe of the Iroquois Confederacy. Douglass Boyd has made a detailed study of the healing practices of the two medicine men and has described the in roads that the traditional religious practices have made into the entire process of healing. Therefore, this traditional practice began with a healing ritual at a conference, sponsored by the research department of the Menninger Foundation and was culminated into two biographies which gave an in-depth account of the importance the environment holds for the medicine men of the two tribes.